Hypoglycaemic Properties of Malaysian Cocoa (Theobroma Cacao) Polyphenols-Rich Extract - Mohd Mokhtar, Ruzaidi Azli (2008)
The objective of the study was to investigate the hypoglycaemic properties of Malaysian cocoa (Theobroma cacao) polyphenols extract in-vivo and insulin sensitivity in-vitro. Cocoa extract (CE) (containing 190 - 286 mg total polyphenol per gram extract) was prepared from fermented and roasted (140°C, 20 min) beans by extracting with 80% ethanol in the ratio of 1 to 10. For the in-vivo study, the CE was administered in three dosages (1%, 2%, and 3%) to groups of normal and diabetic rats for a period of 4 weeks by forcefeeding. Results showed that dosages of 1% and 3% CE significantly reduced (p < 0.05) plasma glucose levels in the diabetic rats. An in-vitro study (BRIN-BD11 cell lines) was used to evaluate the effect of CE on insulin sensitivity. The results demonstrated that CE at a concentration of 0.1 mg/ml significantly increased (p < 0.05) insulin level compared to the control. The results of this study showed that Malaysian cocoa polyphenol extract have the potential of being an insulin-mimetic agent. Further studies are on-going to elucidate the underlying mechanisms of polyphenols present in CE that contribute to the reduction of plasma glucose levels and insulin mimicking activity.